2018
DOI: 10.1080/1331677x.2018.1432374
|View full text |Cite
|
Sign up to set email alerts
|

An empirical analysis of the leader–member exchange and employee turnover intentions mediated by mobbing: evidence from sport organisations

Abstract: Despite the existence of numerous important factors that affect organisations' efficiency and productivity, including leader-member exchange, mobbing, and employee turnover intentions, studies analysing the relationships among these variables are scarce in the sports literature. Hence, the purpose of this study was to investigate the relationships between leader-member exchange and turnover intentions, focusing primarily on the mediating role of mobbing. The sample for the study was collected from participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 58 publications
3
24
0
2
Order By: Relevance
“…Our findings indicate that managerialist employment relations is a function of Nigeria's unique HR practice (and HRM generally) that is steeped in authoritarian, paternalistic, nonparticipatory and unethical HR system (Otobo, 2016;Anakwe, 2002), which is framed by its unique workplace culture that advances the rhetoric of managerialism (Oruh et al, 2018). Consequently, the findings of this research agree with Yildiz's (2018) and Timinepere's (2018) works that turnover intention of doctors is a corollary of managerialist employment relations system. We also found that having a work environment that supports happy workforce, motivation, engagement, participation and empowerment as well as realisation of voice is mediated by participatory and acceptable HR practice.…”
Section: Conclusion Implication Limitation and Further Researchsupporting
confidence: 89%
See 3 more Smart Citations
“…Our findings indicate that managerialist employment relations is a function of Nigeria's unique HR practice (and HRM generally) that is steeped in authoritarian, paternalistic, nonparticipatory and unethical HR system (Otobo, 2016;Anakwe, 2002), which is framed by its unique workplace culture that advances the rhetoric of managerialism (Oruh et al, 2018). Consequently, the findings of this research agree with Yildiz's (2018) and Timinepere's (2018) works that turnover intention of doctors is a corollary of managerialist employment relations system. We also found that having a work environment that supports happy workforce, motivation, engagement, participation and empowerment as well as realisation of voice is mediated by participatory and acceptable HR practice.…”
Section: Conclusion Implication Limitation and Further Researchsupporting
confidence: 89%
“…Interviewees B4, A6, and A1's statements lend credence to this observation. As remarked by Bambacus and Kulik (2013) such HR practices lead to employee turnover intention (Yildiz, 2018). The work by Kim et al (2017) noted that the above climate of inflexible work pattern, lack of satisfaction and managerial system illustrate the essentials of the discontents of inflexible work pattern and consequent employee turnover intention (Joo and Park, 2010).…”
Section: Discontents Of Inflexibilitymentioning
confidence: 97%
See 2 more Smart Citations
“…LMX models represent paramount theoretical and empirical approaches to organizational leadership [32,33] and explain influences on exchange relationship quality and work-related outcomes such as performance and innovative work behaviors [6,21,26]. In particular, the LMX measure incorporates the evolution of leader-follower relationships and followers' satisfaction with their leaders, and addresses a facet of leadership that is absent from other theories-awareness that leaders develop various types of relationships with individual followers [34,35]. Hence, LMX emphasizes reciprocal social exchanges that develop, nurture, and sustain the relationship between a supervisor and their employee.…”
Section: Predictors Of Innovative Work Behaviors: Lmx and Ocbmentioning
confidence: 99%